Elements that influence knowledge sharing in the university-industry-government collaboration: Case studies in Brazil - Igor Junqueira de Castro; Marcelo Seido Nagano; Suzana Xavier Ribeiro (REGE Revista de Gestão, 2019)
Purpose - The purpose of this paper is to determine the factors for an academic research project in electrical engineering to become relevant. Design/methodology/approach - As a conceptual basis, a few theories of entrepreneurial university and triple helix were correlated, seeking to determine the main critical factors and the successful criteria of an academic research project. The research was conducted through four cases of electric engineering that succeed in generating social and economic impact. Findings - When analyzing the available bibliography, it is clear that the connection among the companies, the market and the research that happens at the university is very important. Not only that, but also, according to the results, this is the key to generating revenue and impact on society. In addition, operational policies and competent leaders promoting this impact inside the universities are extremely important. Originality/value - The topic was selected because of the reduced number of articles related to the identification and analyses of the main aspects that make an academic research project relevant to the society. Furthermore, the paper is significant because it analyzes the main factors that help develop a better society and country through academic research.